Productivity and labor politics from the bases: popular technical imagination in the letters to Perón (Quinto Sol, 2020)
This article studies the ways in which public discourses on labor productivity were appropriated, resignified and reproduced by the popular technical imagination during the first presidencies of Juan Domingo Perón in Argentina (1946-1955). As this problem became a priority of the official economic program, its discussion in the press and the publicity of institutional innovations aimed at an improvement in productivity had an impact on the social imaginaries of broad sectors of the population. In letters sent by citizens to Perón with requests, ideas and claims, it is possible to recognize at least three sets of initiatives that address the problem from different perspectives. In a first group are those that, in line with the position of the business chambers, propose as a solution an increase in labor discipline. A second group finds in local technological innovation a way to overcome the difficulty of importing modern machinery in a national context of lack of foreign currency. And finally, a third group overflows the frames of public debate opened by the Peronist government and proposes a refoundation of the institutions aimed at productive innovation from the workers' perspective.
Keywords: popular technical imagination; peronism; productivity; cultural history